Lung Ultrasound in Patients With Dyspnea From Infective Lung Disease - Bracciale, Pierluigi; Bellanova, Salvatore; Cipriani, Cristiana (Frontiers in Medicine, 2021)
Infective lung disease is a spectrum of pulmonary disorders with high prevalence in clinical practice. In the last decade, many studies focused on the clinical usefulness of lung ultrasound (LUS) in the management of patients presenting with dyspnea from infective lung disease. We report data on the methodological and standardized use of bedside LUS in the differential diagnosis of patients with acute dyspnea from infective lung diseases. We performed a cross-sectional study in 439 patients (160 women and 279 men, mean age 64.2 ± 11.5 years, age range 23–91 years) with infective lung diseases. A bedside LUS with a convex probe and chest X-ray were performed in all subjects. Chest CT was performed in a subgroup of patients, as clinically needed. We observed a statistically significant difference in the percentage of pleural effusion and pulmonary consolidation assessed by LUS, compared to X-ray (52.7 vs. 20%, respectively, p < 0.05; 93.6 vs. 48.2%, p < 0.001). The majority of the consolidations detected by LUS were mixed, hypo- and hyperechoic, lesions, with air bronchogram in 40% of cases. All findings assessed by LUS were confirmed by chest CT, when performed. We describe the actual role of LUS in the assessment of patients with infective lung disease. It has higher sensitivity compared to chest X-ray in the detection of pleural effusion. Consolidations from infective lung disease have mostly mixed echogenicity by LUS.